GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 523481798 species occurrences available in GBIF matching the query: TaxonKey: Quercus ilicifolia Wangenh. Year: >= 1980 HasCoordinate: true. The dataset includes 523481798 records from 12346 constituent datasets: 206 records from The Diptera Site. 2618 records from Portuguese Seaweeds. 101 records from Hoher Stein Kallenhardt. 6 records from Boimstorfer Sundern. 1 records from Karpfenteich, Klasse 6d. 27 records from Fluss - Vielfalt. 6680 records from SOMBASE PYCNOGONIDS. 148 records from Hintere Halde. 2157 records from UWYMV Bird Collection (Arctos). 54899 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 480 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 123309 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 119 records from Bryozoa of the British Isles. 1 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 5534 records from Guadeloupe_Herbier. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 19 records from Herbarium WRSL, Flora of the Silesia. 991 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 3633 records from Bioimages. 1 records from DMNH Eggs. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 9636 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 11670 records from Naturalis Biodiversity Center (NL) - Crustacea. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 53985 records from BioMar - LIFE project. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 378 records from Tsetse flies of East Africa update. 40565 records from Oregon State University Herpetological Collection. 623176 records from Fishbase. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 373 records from Otter survey of Ireland 2004 & 2005. 1292 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 127 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 3509 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 26661 records from Plan de vertebrados de la Patagonia. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3586 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 220 records from Phthiraptera. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 61 records from University of Ghent - Zoology Museum - Vertebratacollectie. 74399 records from Marie-Victorin Herbarium (MT). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 27538 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 395 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 346 records from Mycological collection of the National Museum. 3509 records from Entocytheridae (Ostracoda) World Database. 16 records from Siphonaptera. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 1998 records from Aves de la cuenca media del río Bogotá. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 17 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 2700 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 2438 records from Colección de peces dulceacuícolas de Costa Rica. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 201409 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1238 records from Insect Collection (CeStuBio). 18 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 168884 records from Phanerogamic Botanical Collections (S). 81429 records from African Rodentia. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 5371 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 257 records from Colección nacional de palmas de Colombia - JBQ. 11 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1168 records from Colección de Entomología - Diptera - Ceratopogonidae. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 353 records from Coastal and marine species. 2706 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 1485 records from IWDG Constant Effort Cetacean Sighting Scheme. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 8658 records from Mollusca collection of National Museum of Nature and Science. 104 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 5709 records from Coleoptera of Piska Forest. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 310 records from WNMU Fish Collection (Arctos). 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 1702 records from BioGIS - Bryophytes - HUJ collections. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 38648 records from Marine species distributions in Irish coastal waters. 2546 records from The atlas of butterflies in Kraków. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 89874 records from ecoscope_observation_database. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 11391 records from JOI - Herbário Joinvillea. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 8220329 records from OEH Atlas of NSW Wildlife. 9858 records from ISE - Herbário ISE. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99300 records from Landesmuseum Kärnten. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 21679 records from HUEM - Herbário da Universidade Estadual de Maringá. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 561 records from CSUC Vertebrate Collection. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 2922 records from National Lesser Horseshoe Bat Database. 20 records from Truchas Mexicanas. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 191 records from Herpetofauna laguna El Tinije. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 64603 records from HUFU - Herbarium Uberlandense. 19 records from Revision von Suctobelba trigona (Michael, 1888). 3 records from MSB Mammal Observations (Arctos). 228 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 106428 records from Jordal. 510690 records from MVZ Herp Collection (Arctos). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 57492 records from PRECIS (KwaZulu-Natal Herbarium). 355 records from Herbier G. Garapin (BOUM). 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 9302 records from Ants from the Paraguayan dry Chaco. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 10633 records from Biological Records Centre - Collembola Recording Scheme. 4826 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 73327 records from University of Vienna, Institute for Botany - Herbarium WU. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 433964 records from MVZ Mammal Collection (Arctos). 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 117692 records from Australian National Wildlife Collection provider for OZCAM. 3204 records from Faunal Inventory of Morysin Nature Reserve. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 288 records from Fungi of Słowiński National Park, Poland. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 2996 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 12065 records from Tromsø Museum, Bryophytes. 53815 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 9809 records from UFG - Herbário da Universidade Federal de Goiás. 443 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 47 records from Guyane_française_caféier. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 833 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 10358 records from Census of the flora of Benin. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 356 records from Morphologische Daten von Puffinus creatopus. 3 records from Reptilia Collection of Museum and Institute of Zoology PAS. 4631 records from Southern Cape herbarium. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 7 records from Order Diptera, family Mydidae. 6335 records from Herbarium Vonderau - FULD. 26141 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1 records from Newly discovered sister lineage sheds light on early ant evolution. 1020709 records from Consortium of California Herbaria. 12661 records from CCBER Herpetology Collection. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 45443 records from IAC - Herbário do Instituto Agronômico de Campinas. 60670 records from QLD DERM Coastal Bird Atlas (Trial). 551213 records from Bee Biology and Systematics Laboratory. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 29 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 48564 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 7892 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 5733 records from Small Mammal Research Database. 1 records from Red list project inventory, bryophytes. 485 records from National Taiwan Ocean University. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 1 records from Lissotes working-group. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 31 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 30872 records from Online Atlas of vascular plants 2012-2020. 8958 records from SANT-Lich. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 226 records from Collection of Heteroptera. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 183 records from Collection entomologique Pierre Lachiver. 24268 records from Zoology (Museum of Evolution - Uppsala). 899760 records from Naturalis Biodiversity Center (NL) - Botany. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 14 records from Type Specimen Database of Museum and Institute of Zoology PAS. 28315 records from SANT-Algae. 6237 records from Plecoptera. 1324 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 1017 records from Irish Marine Turtle Database. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 34 records from New records in vascular plants alien to Kyrgyzstan. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 11638 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 3091617 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 7421 records from Weevils of the Tatra Mts.. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 458185 records from Bird Atlas 2007 - 2011. 3076 records from dec2011. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 57845 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1214311 records from AntWeb. 825 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 177466 records from CAS Entomology (ENT). 474 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 39295 records from SPSF - Herbário Dom Bento José Pickel. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 1174 records from PReCAST Marine Mammal Sightings. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 2494 records from Marine Environmental Monitoring - Marine Turtles. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 27670 records from CSIRO Ichthyology provider for OZCAM. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 4146 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 227 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 264 records from Entomological collection of the National Museum. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 3276 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 59792 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 7693 records from NHM, Heteroptera. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 1137 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 19555 records from KUBI Ornithology Tissue Collection. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 125939 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 917964 records from PRECIS. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4415 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 1 records from Taxonomic review of the genus Wasmannia.. 17618 records from BioGIS - Mammals - INPA database. 26104 records from SPF - Herbário da Universidade de São Paulo. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 17012 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 49678 records from SANT herbarium vascular plants collection. 2513 records from Carabidae of the Tatra Mts.. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1163 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 212 records from Irish Federation of Sea Anglers Catch Data. 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 13863 records from Albany Museum. 6541 records from Likona Invertebrates. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 28788 records from EPA River Biologists data. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 73408 records from SAIAB. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 50000 records from observe_tuna_bycatch_ecoscope. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 190 records from Relative abundance of ostracods in sediment core Sv09. 1150 records from Paläontologie Marburg. 1319 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 3 records from Collection Myriapoda - SNSD. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 165322 records from KUBI Mammalogy Collection. 4447 records from Lepidoptera (Observations). 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 3182 records from Finnish Entomological Database: Heteroptera. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 1526 records from University of Amsterdam (NL) - Páramo pollen reference collection. 61 records from Registros restauración ecológica- Magdalena medio. 45718 records from Colección Herbario Federico Medem Bogotá - FMB. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 4250 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 20 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3978 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 154 records from Perot Museum of Nature and Science. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 4311 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 599260 records from FLORIVON. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 387501 records from Species data extracted from the National Vegetation Database. 35697 records from Sphaeroceridae Collection. 10606 records from Cercle des mycologues de Montréal Fungarium (CMMF). 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 1854895 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 331 records from Guadeloupe_Bananier. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 9349 records from Harriet Irving Botanical Gardens (HIBG). 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 15 records from Projeto Abrace o Boto Cinza. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 355 records from Colección de Entomología - Arthropoda. 44982 records from UFP - Herbário UFP - Geraldo Mariz. 3312 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 349 records from Insect Collection from New Caledonia. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 31845 records from NPL collections. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 3522 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 7671 records from HERBAM - Herbário da Amazônia Meridional. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 4217 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 75092 records from Herbario Universidad de Antioquia (HUA). 634166 records from Inventario Español de Especies Terrestres (MAGRAMA). 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 77 records from Empria and Monsoma in Japan. 25 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 654 records from Helgeland Museum, Tabanidae. 2011 records from Local BioBlitz Challenge 2013. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 4289 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 23334 records from Herbario Pontificia Universidad Javeriana. 2107 records from MLZ Mammal Collection (Arctos). 29462 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 88290 records from URM - Herbário Pe. Camille Torrand. 751 records from Trichoptera (caddisflies) of Ireland. 1 records from On centipedes (Chilopoda) of Albania, 2. 3 records from Note su alcune specie di chilopodi della regione palestinese. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 1024 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 382 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 19127 records from Biological Records Centre - Cerambycidae Dataset. 102438 records from ICN - Herbário do Instituto de Ciências Naturais. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 4 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 834 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 63 records from (Data S1) Palynology of ODP Site 119-739. 6766 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 31 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 14 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 73901 records from NCSM Fishes Collection. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 256 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 219 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 1329 records from API_CRSN_Data. 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 24133 records from IICT Herbário LISC. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 6186 records from Chinese mitten crab (Eriocheir sinensis) occurrences in Flanders. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 4369 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 374 records from published_chenopodium_vulvaria_observations. 46 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 32 records from Archaea Collection in BCRC. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 67708 records from University of Alberta Vascular Plant Herbarium (ALTA). 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 368 records from Collection Crustacea - KAUMM. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 1690 records from Colección de Reptiles del Instituto Alexander von Humboldt. 956 records from National Museum of Marine Biology and Aquarium. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 75221 records from Hymenoptera specimen database of Kyushu University. 52 records from Isotope tracer experiment: meiofauna counts. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 5053399 records from Southern African Bird Atlas Project. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 2557 records from Hosted Invertebrate Collection 01. 4855 records from University of Alberta Museums, Entomology Collection. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 4864532 records from Australia's Virtual Herbarium. 3257 records from fundiv france database. 1 records from Herpetology. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 797 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 69797 records from Lepidoptera collection, Natural History Museum, University of Oslo. 3661250 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 618 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 59078 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 253084 records from Lyman Entomological Museum (LEMQ). 17802 records from The Bat Conservation Trust - Colony Count Survey. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 11839 records from Collection of Coleoptera. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 537 records from Ascomycetes of Russian Fennoscandia. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 69 records from Lassentiner Moor (Niepars). 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 2591 records from UAFMC Fish. 119366 records from The digitization of plant specimens of NTU. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1626459 records from SA Flora (BDBSA). 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 253 records from UAFMC Birds. 86556 records from NINA Vanndata øvrige arter. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 56095 records from Albany Museum Grant. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 224 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 68 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 1074 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 32 records from Fundación Miguel Lillo - Colección Invertebrados. 9112 records from UAM Fish Collection (Arctos). 5788 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 917 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 582 records from Bioblitz 2013 Copenhagen Denmark. 9879 records from Bibliographic records of Angola mammals. 1364 records from Irish Collembola records. 1559 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 201 records from BioAcoustica: Wildlife Sounds Database. 4 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 34 records from Sipuncula collection of National Museum of Nature and Science. 588 records from Relative abundance of ostracods in sediment core Lz1120. 987 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 26624 records from Monitoring data from the federal state Bavaria (Germany). 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 52 records from CIM Specimens. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 364 records from Colección Herpetológica de la Patagonia. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 45 records from CHAS Vertebrates. 1481 records from Reptilia notes, NTNU, Trondheim. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 13 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 1826 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 12512 records from ULg_Hexapoda. 2880 records from Coleoptera, NEF. 1 records from Phytochorologie des départements français. 11 records from Pollen profile from sediment core AV14_K2-4. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 3956 records from SMDB - Santa Maria Departamento de Biologia. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 203672 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 6 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 15570 records from Vertebrats d'Andorra. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2847 records from Kangawalla Bird Sightings. 17 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 33521 records from Dragonfly Ireland. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 313 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 70127 records from DMNS Bird Collection (Arctos). 3688 records from Clare Biological Records Centre dataset. 12294 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 255 records from GENT Lactarius Deliciosi. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 228 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 455 records from Aschelminth collection of National Museum of Nature and Science. 302790 records from BioFokus. 23501 records from Amphibian Specimens. 355 records from Culture Collection of Cryophilic Algae. 767 records from BioGIS - Bats - Asaf Tsoar database. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 80737 records from natagora-earlybirds. 443 records from The Fish Collection at the Zoologische Staatssammlung München. 363271 records from University of Florida Vertebrate Paleontology. 49463 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 755 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2613 records from TTRS Ornithology. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 71655 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 1086 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 109 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 13716 records from OUPR - Herbário "Professor José Badini". 48 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 895 records from Lichen.ie Data. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 115 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 330 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 1 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 397 records from Danish Lacewings (Neuroptera). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 52335 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 2357 records from MISE Project Otter Records, 2011-2015. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 58 records from Mamíferos laguna El Tinije. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 26566 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 571 records from Collection of Hymenoptera. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 5538 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 2 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 146 records from Megophthalmidia_of_North_America. 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 27167 records from Bird tissue collection, Natural History Museum, University of Oslo. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 15879 records from HAMAB - Herbário Amapaense. 820550 records from Fauna Atlas N.T.. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 245 records from Kiesgruben Wemb. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 118357 records from NINA insect database. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 10052 records from CUMV Mammal Collection (Arctos). 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 114472 records from UAM Mammal Collection (Arctos). 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 7410 records from Helgeland Museum, Lepidoptera. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 22585 records from CUMV Fish Collection (Arctos). 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 133313 records from Field Museum of Natural History (Zoology) Bird Collection. 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 29263 records from Tromsø Museum, Fungi. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 59493 records from Irish Vascular Plant Data - Paul Green. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 80 records from HSU Wildlife Eggs and Nests. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 464 records from Lepidoptera collection, NTNU, Trondheim. 9537 records from Herbier du Bénin. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 711 records from Odonata collection, NTNU, Trondheim. 2327 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 519290 records from Museum Victoria provider for OZCAM. 20600 records from Butterflies of Ireland. 461 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 314 records from Peces laguna El Tinije. 59 records from European bison in Białowieża Primary Forest. 1748 records from Harvestmen_of_French_Guiana. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 94 records from LISU Herbario Angola. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 378 records from CCBER Mammalogy Collection. 3 records from MfN - Micropaleontology. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 2940 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 268640 records from MBM - Herbário do Museu Botânico Municipal. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 102 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 163444 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 20 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 19 records from Counts of benthos communities in Kongsfjorden in 2009. 136 records from Plants galls. 41438541 records from Artdata. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 99070 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 32346 records from CRCM Vertebrate Collection. 3 records from Diatom abundance of Hole 38-338, Part 2. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8579 records from The atlas of breeding birds in Małopolska. 71 records from (Data S1) Palynology of ODP Site 113-696. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 1794 records from Flora of tanzania. 7 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 48310 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 988 records from PSUZC-Amphibians Collection. 2815 records from Helgeland Museum, Araneae. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 18579 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 9088 records from Flora of Słowiński National Park, Poland. 1754 records from Eggs Specimen. 64882 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 14587 records from Cowan Tetrapod Collection - Mammals. 764 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 10923 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 1905 records from BioGIS - Reptiles - INPA database. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 772 records from INRA-Versailles Arabidopsis natural variants. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 8583 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 2334 records from Ohio University Invertebrate Paleontology Collection. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 5377 records from Herbario Museo de La Salle Bogotá (MLS). 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 21289 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 7756 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 4128 records from Algae (S). 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 805 records from HSU Wildlife Mammals. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 27290 records from Bird Monitoring Data. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 62015 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 2 records from Collection Crustacea - ZSRO. 119 records from Various insect orders, NEF. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 2290 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 2 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 3 records from Ichthyologie ZMK. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 10284 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 1 records from Vermes ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 553 records from Crustacea ZMK. 3 records from Mammalogie ZMK. 1 records from Cnidaria ZMK. 16 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 3 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 3720 records from Saproxylic Beetles of Ireland. 10651 records from Danish Plant Bugs (Miridae). 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 2 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 19633 records from Endemic plants of the Congo basin. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 882299 records from SA Fauna (BDBSA). 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 11762 records from Chrysomelidae of the Carpathians. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 2 records from Araneae Collection. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 146809 records from OHN. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 170945 records from Field Museum of Natural History (Zoology) Mammal Collection. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 201 records from MVZ Hildebrand Collection (Arctos). 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 53587 records from Lund Museum of Zoology (MZLU). 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 4926 records from Fungus herbarium, UiB. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 1129 records from Upper Silesian Museum, Insect Collection. 2913345 records from Especímenes INBio. 51 records from Packer Collection / Xenochilicola bees, Chile. 13 records from Ornithologie ZMK. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 3221 records from Road Kill Survey. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 25 records from Schwedische Oribatei (Acari). III.. 5842 records from FCAB - Herbário Friburguense. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 32109 records from Herbier de Nouvelle-Calédonie. 1 records from Pantopoda SMF. 7551636 records from BirdLife Australia, Birdata. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 635514 records from Donnees ONF Faune-Flore-Fonge. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 5 records from Reptilia ZMK. 29 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 98873 records from CAS Invertebrate Zoology (IZ). 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1 records from On centipedes (Chilopoda) of Albania, 2. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 2 records from Collection Crustacea - PUM. 83679 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 200 records from Zoological collection of the National Museum. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 827 records from Colección Hidrobiológica del Chocó. 15 records from Malakologie ZMK. 6518 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 10192 records from Crustacea collection of National Museum of Nature and Science. 10840 records from Bird skin collection, Natural History Museum, University of Oslo. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 622 records from UCM Bird Eggs/Nests Collection (Arctos). 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 688 records from Algae, Norwegian College of Fishery Science. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 21742 records from Herbarium of the Université Libre de Bruxelles. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 5 records from Echinodermata ZMK. 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 261 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 982 records from Freshwater plants of Cameroon. 3 records from New country records of reptiles from Laos. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 1000 records from Colección Limnológica del Chocó. 1003 records from NCSM PaleoBotany Collection. 749213 records from Historical Bird Atlas. 30 records from Guadeloupe_Taro. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 9948 records from Bees of Canada / Gschwendtner property collection. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 58050 records from Vascular Plant Herbarium, UiB. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 603 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 61 records from Shrews of Poland. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 2077 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 11491 records from NCSM Birds Collection. 5581 records from IWDG Casual Cetacean Sightings. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 24891 records from UAM Bird Collection (Arctos). 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 2470 records from Annelida collection of National Museum of Nature and Science. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 4025 records from CCBER Ornithology Collection. 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 4601 records from Invertebrate collection of University of Oulu Zoological Museum. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 1561 records from Colección de Zoología Invertebrados - Otros invertebrados. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 8401 records from Herbarium areqvipense (HUSA). 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 1531 records from Culture Collection of Algae. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1415 records from Plant observations from Białowieża National Park. 699357 records from Norwegian Biodiversity Information Centre - Other datasets. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 151 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 7 records from (Table 4) New palynological record of sediments from Odderade. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 4328 records from Naturalis Biodiversity Center (NL) - Mammalia. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 832088 records from Museum of Comparative Zoology, Harvard University. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 12134 records from MPM Herpetology. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 1151 records from arim. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 1509 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 12509 records from The Bat Conservation Trust - Hibernation Survey. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 48 records from Tardigrada collection of National Museum of Nature and Science. 2091 records from Naturalis National Natural History Museum (NL) – Coelenterata. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 293298 records from SEAPOP NINA. 29 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1667136 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 4912 records from Herbier de Strasbourg. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 38650 records from Kathryn Kalmbach Herbarium. 6125 records from NMMNH Mammal. 73341 records from Ichthyology Collection - Royal Ontario Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 263 records from Artenvielfalt Kreis Gießen. 36008 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 49 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 6933 records from Natural History Museum Maastricht (NL) - Herbarium. 798 records from Biological Records Centre - Irish Otter Dataset. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 49637 records from Monitoring data from the federal state Hesse (Germany). 732640 records from iNaturalist research-grade observations. 9775 records from Finnish Entomological Database: Hymenoptera. 7598 records from National Taiwan University. 828 records from UCBG TAPIR Provider. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 17 records from Hazel Dormouse in Ireland. 1696 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 163 records from Entomofauna laguna El Tinije. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 153532168 records from EOD - eBird Observation Dataset. 39267 records from Tasmanian Museum and Art Gallery provider for OZCAM. 29 records from Colección Nacional de Heliconias. 27334 records from Kyushu University Museum Coleoptera Collection. 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 642 records from Reunion_Coffea. 26236 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 64 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 250 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 6004 records from Colección Limnológica Universidad de Antioquia. 67350 records from CAS Ornithology (ORN). 606 records from Líquens d'Andorra. 4852551 records from Bird Ringing Centre in Sweden (NRM). 1474161 records from Consortium of California Herbaria. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 1588 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 152790 records from CONN. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 34 records from National System of Protected Areas in Poland - Fungi. 1077 records from BioGIS - Fish - HUJ collections. 66 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 4 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1572 records from Fongs d'Andorra. 152552 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 69 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 579 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 3669 records from ARKO strandeng. 1589 records from Aquatic Oligochaeta of Ireland. 25204 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 6 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 19634 records from H.A. Stephens Herbarium. 2 records from A new ant genus from the southwestern United States.. 8518 records from Upper Silesian Museum, Bird Observations. 9818 records from NYSM Birds. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 2 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1712 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 304689 records from Aranzadi Ringing Scheme (bird ring-recovery data). 135 records from UCM Vertebrate Observations Collection (Arctos). 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 1072 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 309 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 63267 records from Recent Invertebrates Specimens. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1313 records from Birds collection of Abiko City Museum of Birds. 19464 records from Hemipteran specimens of Iwate Prefectural Museum. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 10866 records from Heteroptera of Ireland. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 470 records from Spiders_of_French_Guiana. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 21868 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 360 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 1789 records from Birds collection of Yamashina Institute for Ornithology. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 17 records from Musée Vert ornithology collection. 10050 records from KUBI Ichthyology Tissue Collection. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 18056 records from University of California Museum of Paleontology. 31259 records from SABCA. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 419514 records from Meadow and Pasture Inventory (SJV). 55 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 33 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 181 records from Alien Species in Poland - Animals. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 1035 records from National Museum Of Marine Science & Technology. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 2882 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 21188 records from National Bat Database of Ireland. 33 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 4627 records from Coleção de Polychaeta do Museu Nacional. 92 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 492 records from Flora of Japan Specimen Database. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 8390 records from University of Lethbridge Herbarium (LEA). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 111886 records from Invertebrates Collection of the Swedish Museum of Natural History. 1900 records from Fungi Collection. 110017 records from Louisiana State University Herbarium - Vascular Plants. 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 33173 records from Global Lacustrine Diatoms. 83546 records from UCJEPS TAPIR Provider. 1727 records from Herbier National de Mauritanie (HNM). 2966 records from Bolivian Amazon lowland fish metacommunity data. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 98 records from Macrophytes_CLF. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 1447 records from Odonata of the Congo River 2010 expedition. 1244 records from Mosquitoes_of_French_Guiana. 9678 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 5787 records from HUSC - Herbário Unisanta. 243739 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 8441 records from Natural England - Batsites inventory for England. 3820 records from Collection entomologique Barthélémy. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 11 records from Pollen profile from sediment core AV14_K2-1. 3330 records from Herbier A. Le Grand (BOUM). 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 8706 records from NINA botanical collection. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 42004 records from Mammals housed at MHNG, Geneva. 3629 records from Wildbook for Whale Sharks. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 73166 records from ALCB - Herbário Alexandre Leal Costa. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 32002 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 106011 records from mel. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 613 records from Countryside Council for Wales - Shad Monitoring data. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 40 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 196 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 18004 records from Census of the animals of Benin. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 353 records from DMNS Marine Invertebrate Collection (Arctos). 84521 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 23803 records from rmca-albertine-rift-butterflies. 8097 records from HPBR - Herbário Padre Balduino Rambo. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 1265 records from Actinomycetes Collection in BCRC. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 174490 records from CAS Ichthyology (ICH). 2477 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 39 records from ECOCEAN MantaMatcher. 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 1117 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 3327 records from BioGIS - Mammals - SPNI. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 17447 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 1474 records from Herbarium Rhoenmuseum Fladungen. 152495 records from Essig Museum of Entomology. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 2013319 records from NMNH occurrence DwC-A. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 7 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 252060 records from Moths Ireland. 7491 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 23386 records from NCSM Vertebrate Paleontology Collection. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 39766 records from BioGIS - Vascular plants - A. Danin's point database. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 1552 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 128 records from Birdrace-Brut-Wetteraukreis. 120 records from Birdrace-Kosmos_Racer-Freising. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 114 records from Birdrace-Finkenspötter-München. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 112 records from Birdrace_Die_Borner-Viersen. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 108 records from Birdrace-TriumVIErat-Viersen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 95 records from Birdrace-Buteo1_DO-Dortmund. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 127 records from Birdrace_Schräge_Vögel-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 1838 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 24819 records from DMNS Mammal Collection (Arctos). 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 110 records from Birdrace-LiLaMai-Vechta. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 103 records from Birdrace-Die_Nachtigallen-Herford. 360 records from Küstenschutzwald. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 37 records from Berlin - Treptower Park / Karpfenteich. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 25883 records from Monitoring data from the federal state Saxony (Germany). 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 951 records from Literature based species occurrence data of birds of North-East India. 109 records from Birdrace-Team_Charadrius-Günzburg. 96 records from Birdrace-federleser-Herford. 92 records from Birdrace-Team_BO-bachter-Bochum. 91 records from Birdrace-Enger_am_Spektiv-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 162 records from Siegen/ Gymnasium Am Löhrtor. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 151 records from Isarufer. 55 records from Waldsee. 113 records from Hochschulgelände (Bremen). 46360 records from TNHC Ichthyology Collection. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 18847 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 111 records from Birdrace-Uhulogen-Lippe. 105 records from Birdrace-ARKONAuten-Rügen. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 101 records from Birdrace-Herford-Birder-Herford. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 76 records from Birdrace-Birding_for_Nature-Bonn. 59 records from Im Bauerngarten. 185 records from Klasse 3a. 342 records from Kremmer Luch. 271 records from Beweidungsprojekt an der Nesse. 122 records from Kloster Eberbach. 97 records from LauWi. 144 records from Ehmkendorf. 57 records from Heidesee / Halle. 145 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 100 records from Birdrace-Meister_der_Herzen-Kleve. 85 records from Birdrace-Die_Paradiesvögel-Herford. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 426 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Borkhart. 114 records from Flora. 100 records from Feriendorf Ober-Seemen. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 44 records from "Schlechteberg" Ebersbach/Sa.. 84 records from Roter Berg Werdau (Leubnitz). 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 45 records from Flusswerder in der Weser (Hameln). 66 records from Wedeler Au. 150 records from Steinbruch Mainz-Weisenau. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 241 records from BIRDRACE RennVögel Münsterland. 257 records from Seewasen. 198 records from FNL e.V.. 83 records from Spechtwald. 80 records from Förderzentrum Schmölln. 100 records from Grenzturm Hohen Neuendorf. 70 records from Lech 2001. 52 records from Fledermaus. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 101 records from Naturgrundstück (Eutin). 69 records from Schulgarten mit Klasse 8a (Essen). 97 records from Döchtbühlwald (Bad Waldsee). 233 records from Föhrenried (Fronreute und Baindt). 15 records from AKG-Bensheim. 270 records from Regenrückhaltebecken (Zeulenroda). 20 records from Motzener Tonsee. 313 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 39 records from Südpark (Bochum-Wattenscheid). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 56 records from Zitadelle Berlin-Spandau (7b). 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 46 records from Hainbachtal in Oelsnitz/V.. 308 records from Wangerooge. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 149 records from Wirbach. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 113 records from Rund um das LUGY. 50 records from Junge Heide, Radebeul/Dresden. 85 records from Insektenvielfalt Ahe/Weichelsee. 12 records from Kindergarten. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 282 records from Deponie Klausdorf. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 170 records from Bodenseeufer Radolfzell. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 95 records from Ortelsbruch - Hangmoor bei Morbach. 6443 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 22 records from Dellwiger Bach (Dortmund). 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 161 records from Schussenaue bei Berg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 106 records from Schulgarten Hans-Carossa-Oberschule. 54 records from Ludwigshofen. 107 records from Landschaftsschutzgebiet Buchhorst 3. 18 records from Spielwiese. 9 records from Willersalpe. 103 records from Schwanseepark (87645 Schwangau). 48 records from Trockenrasen bei Dörndorf. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 23 records from Alter Nördlicher Friedhof (München). 167 records from Zielbach (Töll). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 325 records from Triebesbach (Zeulenroda-Triebes). 62650 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 145 records from privater Garten. 31 records from Nationalpark Harz Schul-AG Braunlage. 18 records from Mittelstreifen. 108 records from Mainufer. 59 records from Rund ums Ökohaus (Würzburg). 28 records from Sandgrube Zaisertshofen. 54 records from Wiese am Unterbecken. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 41 records from Örtzemündung (Stedden). 101 records from Naturhausgarten. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 86 records from Alter Kreidebruch Saßnitz/Rügen. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 71 records from Bolzplatz. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 219 records from Umgebung der Grundschule Oderberg. 96 records from Die Wuhle. 180 records from Paul-Gerhardt-Schule Dassel. 122 records from Stever. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 73 records from Varnhalt. 32 records from Schulhof Sandhofenschule (Mannheim). 163 records from Brander Wald (Stolberg). 99 records from Düne am Ulvenberg (Darmstadt). 111 records from Ökologischer Weinberg (Guntersblum). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 77 records from Trockenrasen Franzigmark (Halle/Saale). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 139 records from NSG Leist bei Ziegenhain. 245 records from Gieselbachtal Fulda-Harmerz. 94 records from Kochertgraben II. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 117 records from Wassermann. 79 records from Balkon (Norderstedt). 181 records from Spießwoogtal / Königsbruch (Fischbach). 103 records from Wasserwerkspark (Chemnitz). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 160 records from Wirbach-Taubental (Bad Blankenburg). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 17 records from Schutzgebiet Ochtersum. 22 records from Heilpflanzen im Hainbachtal. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 110 records from Obstwiese Osterberg. 59 records from Oschenberg, NO von Bayreuth-Laineck. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 19 records from Goethe-Hauptschule/Projekt I-10. 79 records from GymnQuerfurt. 54 records from Zentralfriedhof (Wien). 63 records from Erft in Selikum (Neuss). 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 124 records from Wiesenbiotop am Wasserturm. 212 records from Artenvielfalt im Beckerbruch (Dessau). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 98 records from Warnowtal (Rostock). 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 98 records from Rund ums Cani. 54 records from Weidegebiete in der Selzrenaturierung. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 35 records from Urwald 3 (Bad Waldsee). 65 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 99 records from Dorfrand Mauderode. 50 records from Artensuche auf den Elbwiesen in Radebeul. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 40 records from Flächennaturdenkmal Grubditz. 62 records from Amtsrain Apolda-Zottelstedt. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 214 records from Binsenwiesen. 155 records from Bammentaler Duft- und Heilkräutergarten. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 101 records from Isartal Dingolfing. 58 records from Weidewirtschaft. 783 records from Moluscos Marinhos de Augusto Nobre. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 4 records from Schulbiotop und Brigach (Villingen). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 1 records from Revision of the Nearctic endemic Formica pallidefulva group.. 22 records from Breitkopfbecken (Berlin-Reinickendorf). 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 95 records from Vielfalt verschiedener Wiesen. 53 records from Weidegut Rechab. 147 records from NABU-Auerochsenweide. 107 records from vegoek. 153 records from Selztal bei Friesenheim. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 28 records from Uferzone Wipper (Biesenrode). 61 records from Artenvielfalt auf der Wiese. 43 records from Saalewiesen Naumburg. 55 records from Flora und Fauna am Mittelrheintal. 60 records from Schafsweide Seniorenhaus Berghof. 244 records from WildesMoor bei Schwabstedt. 92 records from Birkenloh. 172 records from Dalbekschlucht. 93 records from Höltigbaum. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 63 records from Hochschule Zittau/Görlitz. 61 records from GE-Brühl. 47 records from Neanderthal. 86 records from Naturerlebnisraum Koppelsberg (Plön). 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 15 records from Regenwasserabfangsbecken (Erlenbach). 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 193 records from Gelände des Schulzentrums am Himmelsbarg. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 10 records from Feuchtwiesen Wippertal bei Wippra. 134 records from Birdrace-Team_Havelland-Havelland. 155 records from Birdrace-Usedommeln-Ostvorpommern. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 172 records from Leben im Finkensteiner Moor. 133 records from Wulfsmuehle/Pinnau. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 53 records from Bad Bodenteicher Heide. 60 records from NABUGEO1. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 31 records from Kurler Busch (Scharnhorst). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 41 records from Morphologische Daten von Natrix. 221 records from Römertal (Steinpleis). 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 71 records from Birdrace-do_elster_Dortmund. 29 records from Naturerfahrung. 51 records from Schrebergarten Düsseldorf Oberkassel. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 31 records from Regenwasserabfangbecken. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 10 records from Ökowerk Emden. 69 records from Entdeckertour am Muldestausee 1/05. 40 records from Öhmdwiesen und Göldern (Konstanz). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 128 records from Birdrace_turbine_untersee-Konstanz. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 122 records from Birdrace-Hügelland-Mainz/Bingen. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 79 records from Birdrace-Bielefinken-Bielefeld. 23 records from Wiese Niederaula. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 15 records from Bodentiere rund um die Schule. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 207 records from Biosphäre Bliesgau. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 100 records from Birdrace-The_Ringers-Friesland. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 42 records from sbosch. 89 records from Birdrace-Team_Wangerooge-Friesland. 62 records from Zoo Frankfurt. 102 records from Industriebrache (Kempen). 13 records from Garten Hamburg Uhlenhorst. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 39 records from Soolbach-Tal. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 97 records from Landschaftspark St.Leonhard-Deisendorf. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 39 records from Stausee Weiditz. 21 records from Bach. 63 records from Sternwiese Mülheim-Broich. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 87 records from Klütwald. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 64 records from Pilzlehrwald. 27 records from Vögel. 57 records from Schulgarten Fichteschule. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 142 records from Kinderbauernhof Pinke-Panke. 24894 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 78 records from Birdrace-Die_Laufenten-Braunschweig. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 57 records from Garten in Schmölln. 36 records from Selz (Ingelheim am Rhein). 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 65 records from LSG "Großes Bruch". 21 records from Riedkanal Bötzingen. 81 records from Birdrace-Die_Ornithomaten-Herford. 54 records from Park Schönfeld (Kassel). 40 records from Schulhof Liebfrauenschule Oldenburg. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 64 records from Schafheide im Böblinger Wald. 15 records from Die geheimnisvolle Welt der Spinnen. 21 records from Tauchen und Meer 02. 4 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 46 records from 8c. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 51 records from Steinbachtal (Würzburg). 81 records from Stadtpark Schmölln. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 36 records from Plöwener Wald. 49 records from Dörnberg. 47 records from Schulgelände Ceciliengymnasium. 4419 records from MVZ Bird Observations (Arctos). 39 records from Regenrückhaltebecken Bad Bevensen. 117 records from Naturschutzgebiet Kochertgraben. 84 records from Streuobstwiese Haus Zeitz. 26 records from Erhard Sopp. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 13 records from Tiere im Teichgebiet. 68 records from Streuobstwiese. 36 records from Olympiapark (München). 23 records from Tümpel Schulbiologiezentrum. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 6 records from Fließgewässeruntersuchung am Haselbach. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 35 records from Gym Freyung. 51 records from Mühlenbach bei Buxtehude. 11 records from Waldgebiet Todtnau- Sonnhalde. 57 records from Mauervegetation,Flechten und anderes. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 27 records from Zwickau- Schwanenteich. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 28 records from Stadtpark Prinzengarten (Sigmaringen). 10 records from schlittschuhweiher. 20 records from Mikroorganismen. 36 records from Salzwiese Diekskiel. 13 records from FND "Weißer Berg" Leißling. 3 records from FFR Hausen. 45 records from Georgs-Padd (Wangerooge). 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 34 records from Wattenmeer-Safari (Wurster Watt). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 10 records from Bachpatenschaft Beeke. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 141 records from Draubiotop Lavamünd. 22 records from Kaltenkirchen Brache. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 17 records from Tierpark Zittau. 6 records from Sächsische Schweiz (Pfaffenstein). 11 records from Privatteich(St.Leon). 94 records from Landschaftsschutzgebiet Buchhorst 4. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 11 records from Vögel im Garten Kindergarten Zaisertshofen. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 22 records from Bachabschnitt der Nette (Osnabrück). 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 81 records from Schulgarten-St.-Georg-Gymnasium. 56 records from Estetal (Buxtehude). 64 records from Issumer Fleuth. 32 records from Nationalpark Harz Juniorranger. 1174 records from Sudeniederung (Amt Neuhaus). 29 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 24 records from Ornithologische Wanderung um Tussenhausen. 12 records from Kinderwald Hannover. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 26 records from Schulteich Heinrich-Mann-Schule. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 23 records from AKG-Gelände in Bensheim. 19 records from Glemstal (Leonberg). 20 records from Lerchenauer Baggersee (München). 80 records from Lahnufer in Villmar. 24 records from Kaisertal. 48 records from Heider Bergsee (Brühl). 15 records from Beisetal bei Niederbeisheim. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 27 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 16 records from Upper Silesian Museum, Bird Collection. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 29 records from Insekten. 719 records from IBF Monitoring of Plant Galls. 8 records from Krittenhorster Wald (Ostkilver). 21 records from LBV-Kindergruppen Markt Tussenhausen. 23 records from Wattuntersuchung (Cuxhaven). 1 records from Graureiher in Lans. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 40 records from Tiere und Pflanzen um uns herum !. 15 records from Kirchheller Heide ( Bottrop). 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Urwald 2 (Bad Waldsee). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 8 records from Eichendorf Weiher Schwalbach a.Ts.. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 13 records from Warnowufer Groß Klein. 9 records from Wiesendreieck Luckenwalde. 16 records from Im und um das Schulhaus. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 18 records from Naturtag. 12 records from Ohemoor (Hamburg/Norderstedt). 15 records from Tiere. 59 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 7 records from Stadtrandlandschaft Apolda-Nord. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 5 records from Feuchtwiese. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 24 records from Tauchen und Meer. 5 records from Schulinnenhöfe (Gelsenkirchen). 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 1 records from Haslauer Moor. 4 records from Neues Testprojekt. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 1114 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 12 records from Schulgelände Erich-Kästner-Schule. 5 records from Fledermäuse u. nachtaktive Insekten. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 89 records from Schulgelände Paul-Gerhardt-Schule. 80 records from Landschaftsschutzgebiet Schmutterwald. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 61 records from Fürstenberger Ralley Teil 3. 15 records from Kühnauer Aue und Kühnauer See. 313 records from BIRDRACE Gätkes Erben. 278 records from BIRDRACE Usedommeln. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 135 records from Waldi-Weiher. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 274 records from Bernhardsthal. 279 records from BIRDRACE Wannacks Topti(c)ker. 256 records from BIRDRACE Upupa epöpse. 157 records from BIRDRACE Rheinische Wasserrallen. 84 records from BIRDRACE Bielefinken. 166 records from BIRDRACE Die Düsselmöwen. 101 records from BIRDRACE Enger am Spektiv. 1 records from Waldtag in und um Seelingstädt. 3 records from Blankenfelder See. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 2 records from Hildener Heide - Spörkelnbruch (Haan). 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 555 records from FFH-Gebiet "Calwer Heckengäu". 13 records from Tag der Artenvielfalt am Bruckenwasen. 371 records from Bannwald Burghauser Forst. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 359 records from Pöhlberg bei Annaberg. 93 records from Haarbach Höfe. 517 records from Schulzentrum "Parc Hosingen". 146 records from LK 11 im Mönchspark. 254 records from BIRDRACE Thüringer Becken-Birders. 1 records from 5. Wiener Gemeindebezirk. 1 records from Fledermäuse über der Alster (Hamburg). 107 records from Müritz-Nationalpark. 52 records from Naturschutzstation Weinberghaus (Dessau). 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 74 records from Schulwald Grundschule Brügge. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 161 records from BIRDRACE Nord-Seh-Team. 269 records from BIRDRACE Kosmos-Racer. 287 records from BIRDRACE Pody und Co. 139 records from BIRDRACE Turbine Untersee. 91 records from BIRDRACE NABU LV Hessen. 91 records from BIRDRACE SchrägeVögel. 95 records from BIRDRACE accipiter hardcore birding. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 169 records from Expedition "Schulgelände". 1177 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 126 records from Schulwald Marksuhl. 144 records from BIRDRACE Die Mohrenlerchen. 65 records from BIRDRACE Federal Birds of Investigation FBI. 69 records from BIRDRACE Pfeifenten. 366 records from Weinberg Reichersdorf. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 369 records from BIRDRACE Havelland. 145 records from BIRDRACE Dith Marsh Sandpiper. 272 records from BIRDRACE Niederlausitz-Team. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 274 records from BIRDRACE Asiola-Quartett. 138 records from BIRDRACE Arkonauten. 258 records from BIRDRACE Raumpatrouille Oriolus. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 80 records from BIRDRACE Falkenberger Fluppis. 131 records from BIRDRACE Brut. 140 records from BIRDRACE Guckers Offenbach. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 82 records from BIRDRACE Buteo2DO. 84 records from BIRDRACE Avinauten. 95 records from BIRDRACE BiBi. 96 records from BIRDRACE OAG Neuwerk. 98 records from BIRDRACE Die Paradiesvögel. 99 records from BIRDRACE TEAM BO-BACHTER. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from BIRDRACE Willi goes Birding. 103 records from BIRDRACE Die Otzberger. 62 records from Hettstadt Gehäge. 82 records from BIRDRACE Die Ziegeneier. 96 records from BIRDRACE Emslandracer. 97 records from BIRDRACE NABUhu Trier!. 100 records from BIRDRACE Stuttgart 100 trööt. 104 records from BIRDRACE Erlanger Piepmätzchen. 105 records from BIRDRACE Kiesmätze. 106 records from BIRDRACE Ave Goettingen!. 111 records from BIRDRACE Die Wendehälse. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 121 records from BIRDRACE Immerwiederhopf. 107 records from BIRDRACE Borussia Zippammer. 2214 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 173 records from FFH-Gebiet Klosterwasser/Burkau. 132 records from Aachtobel. 103 records from BIRDRACE federleser. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 105 records from BIRDRACE coesfelder_vogelkundler. 110 records from BIRDRACE Angeliter Ornis. 109 records from BIRDRACE Die Borner. 402 records from Tag der Artenvielfalt in Heidelberg. 113 records from Tornoer Teich. 62 records from Lebensraum Dorf. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 214 records from Pflanzen und Tiere im Burgwald. 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 102 records from BIRDRACE Westfälische Nachtigallen. 102 records from BIRDRACE Buteo1DO. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 79179 records from All Ireland Non-Marine Molluscan Database. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 120 records from BIRDRACE The early birds. 112 records from BIRDRACE Hügelland zu Fuß. 67 records from Tongrube bei Hettstedt. 145 records from Gronau - auf der Suche nach dem Neunauge. 504 records from Schatzinsel Wangerooge. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 248 records from Schulgarten der Volksschule. 174 records from BIRDRACE Bon(n)apartemöwen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 134 records from BIRDRACE Griffin Wood Warblers. 132 records from BIRDRACE Die Wetterauer. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 126 records from BIRDRACE Duckehühnchen. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 119 records from BIRDRACE Tick, Trick und Track. 115 records from BIRDRACE Die UHULOGEN. 114 records from BIRDRACE Di-Bi-Di-Birder. 112 records from BIRDRACE Gütersloher Gimpel. 107 records from BIRDRACE Herford Birders. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 66 records from Langes Tannen(LMS), Klasse 5d. 37 records from Liether Park 2 (LMS), Klasse 6c. 144 records from Lustbach-Umland. 149 records from BIRDRACE Birding Bentheim. 60102 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 114 records from BIRDRACE VIE will rock you!. 108 records from BIRDRACE Diesmal sehen wir mehr. 44 records from Wiesen am Treffpunkt Freizeit. 121 records from Owere Fiddel. 54 records from VFD-H: MIttelgebirgsweide. 80 records from Feldweg Waldkirchen. 101 records from Steinbruch Kronungen. 66 records from Von der Nutzung zur Natur. 61 records from BIRDRACE Baumläufer. 79 records from BIRDRACE Blinde Hühner. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 176 records from BIRDRACE Professorenteam. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 54 records from Biotope im Schulumfeld. 114 records from Liether Kalkgrube. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 96 records from "Ahrschleife bei Altenahr". 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 90 records from BIRDRACE TicTacToe. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 101 records from IBF Monitoring of Orthoptera. 120 records from BIRDRACE Ornis im Einsatz. 114 records from BIRDRACE LiLaLau. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 47 records from Schulgelände Grolland. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 99 records from Streuobstwiese Stedar. 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 116 records from Sürther Aue. 194 records from Bodenteicher Seewiesen. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 61 records from Wälder im Hainbachtal. 85 records from Ober-Olmer Wald. 54 records from Wir erkunden die Hofau, Klasse 5c. 29 records from Waldwiese. 49 records from VFD-H.: Rheingau: Bärstadt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 36 records from Liether Park 1 (LMS), Klasse 5b. 269 records from BIRDRACE Dithmarscher Deichhühner. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 104 records from BIRDRACE Andechser Stativträger. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 85 records from Rund um den Hainbergsee. 269 records from BIRDRACE speedbirder. 76 records from BIRDRACE Nachtigallen. 88 records from BIRDRACE Kingfisher. 106 records from BIRDRACE Die Schwenker-Birder. 177 records from BIRDRACE Mehr Seh Team. 101 records from BIRDRACE nabu-rhein-main.de. 102 records from BIRDRACE Niederrheinische Bartgeier. 110 records from BIRDRACE Linumer Luchschleicher. 120 records from BIRDRACE Die TUErteltauben. 57 records from Schulgarten Janusz-Korczak-Realschule. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 45 records from Reusaer Wald. 58 records from Schulgarten Zinnowwald-GS. 83 records from BIRDRACE Die Frankenpfeifer. 84 records from BIRDRACE Birding for Nature. 143 records from BIRDRACE Die Laufenten. 69 records from Unter hellen Zinnen und finsteren Grotten. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 52 records from Aktion der Klasse H2 in Simmelsberg. 6325 records from Colección Entomológica de la Universidad de Antioquia. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 53 records from BIRDRACE Taubenhaucher. 63 records from Rosarium (LMS), Klasse 6a. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 17 records from Nachtinsekten am Muldenufer. 192 records from "Schwarzwassertal" bei Pobershau. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 277 records from Colección de Entomología - Auchenorrhyncha. 18 records from Landschaftsschutzgebiet Buchhorst2. 94 records from FFH-Gebiet Paartal. 30 records from Geführte Wanderung im Eselsbachtal. 84 records from BIRDRACE Vogelscheuchen. 48 records from Wahner Heide LK 12 Biologie. 152 records from BIRDRACE NAJU-Aspach. 5739 records from NX - Herbário Nova Xavantina. 146 records from BIRDRACE VdW Wilder Westen. 38 records from Was lebt in der Brutzwiese?. 27 records from Schulgarten Waldorfschule Hassfurt. 75 records from BIRDRACE Die Kartoffelsäcke. 2070 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 17 records from Bachrenaturierung Littfe. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 30 records from Leben auf einer Sturmfläche. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 69 records from BIRDRACE Mathilden-Käuze. 88 records from BIRDRACE Vogelkucker. 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 31 records from Düpenauwiesen. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 33 records from Schüler erforschen die Helme-Aue. 40 records from BUND Naturschutzzentrum St. Julian. 12 records from Art´n Vielfalt im Kinderwald. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 18 records from Schulgarten der Gesamtschule Am Heidberg. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 30 records from Riekdahler Wiesen. 51 records from Kindervilla Außengelände. 61 records from (Table 1) Sedimentology of core D11957P. 5477 records from Colección de mamíferos de la Universidad del Valle. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 7938 records from European riparian ground beetles. 7 records from Die Bachspezies. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 30 records from Höhle am Neuweg / Sächsische Schweiz. 1 records from Streuobstwiese Alt Necheln. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 12 records from Flora und Fauna am Mühlberg. 77 records from VFD-RP: Taunus: Mähweide Dehe. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 837 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 75 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 1385 records from NRM-Herpetology. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 30-63 µm fraction. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 349 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 684 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 273 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 69 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 322 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 432 records from Benthic foraminifera counts of sediment core PS1246-4 (GIK23246-4). 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 116 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 733 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 2 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 663 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 549 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) counts of benthic foraminifera, SE France. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) benthic foraminifera. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 477 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 745 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 144 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction 63-150 µm. 7765 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 1242 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 3492 records from Species counts of benthic foraminifera of sediment core BOFS5K. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 129 records from Abundance of living benthic foraminifera in sediment core CD86_01_BC1. 66 records from Abundance of living benthic foraminifera in sediment core CD86_03_BC4. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 4 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 30-63 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 345 records from Diversity of benthic foraminiferal faunas and benthic foraminifera accumulation rates of ODP Site 184-1143. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction 63-150 µm. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 44245 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 41 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC469. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 313 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 11 records from Schmidt Museum of Natural History_Birds. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 67 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, 63-150 µm. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 134 records from Number of dead benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 166 records from Assemblage of living benthic foraminifera in sediment core GeoB3725-1. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 347 records from (Table 4) Standing stock values of important species in surface sediments. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 206 records from Total foraminifera counts from multinet M31/3_MSN907. 69 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 65 records from (Table 4b) Downcore distribution of live benthic foraminifera of sediment core SW_3b, California continental borderland. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 516 records from (Appendix B1) Calcareous nannofossils of ODP Site 208-1262. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 77 records from Faunal assemblage of sediment core GS7603-12. 70 records from Faunal assemblage of sediment core GS7603-14. 76 records from Faunal assemblage of sediment core GS7603-8. 72 records from Faunal assemblage of sediment core TR149-35. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 76 records from Faunal assemblage of sediment core GS7603-10. 148 records from Faunal assemblage of sediment core GS7603-11. 75 records from Faunal assemblage of sediment core GS7603-9. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 75 records from Faunal assemblage of sediment core TR149-32. 6278 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 124 records from Stable isotope data and sedimentology of core SO42-74KL. 587 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 96 records from Total foraminifera counts from multinet M31/2_MSN894. 128 records from Total foraminifera counts from multinet M31/2_MSN895. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 73 records from Faunal assemblage of sediment core GS7603-13. 76 records from Faunal assemblage of sediment core TR149-37. 66 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 915 records from (Appendix Table 2) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 179 records from Total foraminifera counts from multinet M31/3_MSN906. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 891 records from Benthic foraminifera accumulation rate of sediment core MD01-2378 during marine isotope stage 3. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 2464 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 269 records from Distribution of planktic foraminifera of sediment trap NB6. 152 records from Faunal assemblage of sediment core TR149-38b. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 734 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 359 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in
Keywords: GBIF; biodiversity; species occurrences